Antioxidant Activity of Red Ginger Kombucha (Zingiber officinale var. rubrum) with Various Fermentation Time and Palm Sugar Concentrations - Choirunnisaa, Nadia Maharani Jasmine; Jannah, Siti Nur; Lunggani, Arina Tri; Pujiyanto, Sri; Kusumaningrum, Hermin Pancasakti (Journal of Applied Food Technology, 2025)
The use of red ginger (Zingiber officinale var. rubrum) as the primary ingredient of kombucha is a diversification to increase the antioxidant activity of kombucha. The presence of gingerol dan shogaol in red ginger acts as a potential antioxidant, while the use of palm sugar serves as an additional source of antioxidants and alternative source of sucrose from regular granulated sugar. The fermentation time and the amount of sugar used are two variables that affect the kombucha’s fermentation process. This study aims to examine the effect of various fermentation times and palm sugar concentrations on the antioxidant activity, pH, alcohol content, and organoleptic properties of red ginger kombucha. The methods used were antioxidant test with DPPH, pH test, alcohol content, and organoleptic test with 20 panelist. The results indicate that variations in fermentation time and concentration of palm sugar have a significanr effect (α = 0.05) on the antioxidant activity with IC50 values ranging from 27.89 ppm to 46.77 ppm, categorized as very strong antioxidant activity. The characteristics of red ginger kombucha includes pH 3.6 to 4.6, alcohol content 0.2% to 0.3%, and organoleptic properties varying from moderately liked to liked. Red ginger kombucha fermented for 12 days with 20% palm sugar showed an IC50 value of 40.28 ppm, which categorized into very strong antioxidant activity and is most preferred by the panelists with organoleptic scores of color attribute at 4, aroma at 3.65, and taste at 4.